Pertumbuhan Beberapa Varietas Jagung Manis yang Ditambahkan Bioamelioran - Astiko, W; Isnaini, M; Fauzi, M Taufik; Muthahanas, I (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Astiko W, Isnaini M, Fauzi MT, Muthahanas I. 2022. Growth of several sweet corn varieties added by bioameliorants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 88-96. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Sweet corn is one of the most popular food commodities in the community. However, production is still relatively low. The study aimed to determine the concentration and uptake of N and P nutrients, the development of mycorrhizae, and the growth of several varieties of sweet corn added with bioameliorants. The experimental design used was a randomized block design consisting of four treatments of sweet corn varieties, namely P1: Bonanza variety, P2: Ganebo variety, P3: Golden Boy variety, and F4: Exotic Pertiwi variety. The variables observed in this study were: (1) soil nutrient concentration variables and plant nutrient uptake (N and P) at 42 days after planting (dap), (2) growth variables included: plant height and number of leaves at 14, 28, and 42, and weight of wet and dry root and shoot at 42 dap, and (3) mycorrhizal population variables included: number of spores and percentage of root infection at 42 dap. Observational data were analyzed using analysis of variance followed by the Tukey’s HSD (Honestly Least Significant Difference) test at a significant level of 5%. The results showed that the Golden Boy variety with 25 t ha-1 bioameliorant made from local raw materials gave the highest plant height, number of leaves, wet and dry biomass weight of roots and shoots. While the concentration of total N nutrients, available soil P, plant N and P nutrient uptake, as well as the number of spores, and the highest percentage of mycorrhizal colonization were obtained in the Bonanza F1.